Factors Influencing Gen Z’s Green Product Purchase Behavior - Nisrina Nur Fadhilah; Lale Mega Zahara; Iko Dharma Januar; Dewi Tamara (Green Publisher Indonesia, 2025)
This research examines the increasing awareness and adoption of green products among Gen Z consumers in Indonesia, particularly in Jakarta. Understanding their purchasing behaviors towards green products is crucial in promoting environmentally friendly consumption in emerging markets. Despite the growing interest, it remains unclear whether Indonesian Gen Z is actively shifting their purchases toward green products. This study aims to address this gap by exploring the factors influencing their green purchase behavior. This research specifically investigates the influences on green purchasing decisions among Indonesian Gen Z, a demographic that has not been extensively studied in previous literature regarding green purchase behavior. Data was collected through a self-administered online survey involving 335 respondents. The research employed Partial Least Squares Structural Equation Modeling (PLS- SEM) to analyze the relationships between perceived behavioral control (PBC), subjective norms (SN), green attitude (GA), green branding (GB), perceived environmental responsibility (PER), green packaging (GP), and purchase intention (PI). The findings reveal that green attitude, green packaging, and purchase intention significantly and positively impact green purchase behavior among Gen Z consumers. The study concludes that fostering positive green attitudes and enhancing brand image can significantly encourage green consumption among Indonesian Gen Z. Marketers and policymakers should prioritize these aspects to promote green purchase behavior effectively. This study makes theoretical contributions, as the mentioned literature represents key variables that ultimately lead to green purchase behavior.